Uji Efektivitas Umbi Gadung (Dioscorea HispidaDenust) Sebagai Anti Nyamuk Bakar Dalam Upaya Pengendalian Nyamuk Aedes Aegypti - suherman sohor (STIKes Hang Tuah Pekanbaru, 2021)
Gadung Tuber (Dioscorea Hispida Dennst) containing alkoloid and HCN (Hydrogen Cyanide) which can be used as natural poisons to kill Aedes Aegypti mosquito. This study aims to determine the test of the effectiveness of gadung tuber as anti fuelin the control efforts of aedes aegypti. It wastrue experiment, pre and posttest designs with 5 treatments and 4 times repetitions. The analysis data used the Shapiro-Wilk Normality Test, Homogenity of Variance Test, and One-way ANOVA Test. Total sample was 100 Aedes Aegypti mosquito. The results of this study indicate that the average mortality of mosquitoes at a concentration of 5 mg was 8 tails, a concentration of 10 mg was 16 tails, a concentration of 15 mg was 18 tails and a positive control (Fuel Hit) was 20 mosquito. Anova test results obtained that p-value = 0,000 (p<0,05). Then it can be concluded that from the three concentrations tested 5 mg, 10 mg, and 15 mg, the concentration can kill the Aedes Aegypti mosquito but at different levels of ability. The concentration of 15 mg was declared the most effective in killing the Aedes Aegypti mosquito. Exposure time of 15 minutes was considered the most effective in killing Aedes Aegypti mosquitoes after 4 times repetitions.